Modulation of epithelial homeostasis by HPV using Notch and Wnt - June See Chong; John Doorbar (Tumour Virus Research)
Highly conserved signalling pathways such as Notch and Wnt are essential in the regulation of differentiation and proliferation processes during adult tissue homeostasis. Human papillomaviruses (HPVs) have evolved with humans to manipulate these signalling pathways to establish a basal reservoir of infected cells by limiting HPV-infected keratinocyte differentiation whilst ensuring that differentiating cells are in a replication-competent state. Here, we focus on the canonical Notch and Wnt signalling pathways and their crosstalk to ensure cell-fate lineage determination during epithelial homeostasis. We then examine how HPVs use their E6 and E7 proteins to inhibit differentiation and maintain stem-like characteristics using Notch and Wnt in HPV-infected cells. Determining the functions of E6 and E7 in the maintenance of the infected cell reservoir, and the molecular crosstalk between Notch and Wnt is vital for our understanding of HPV persistence, and may represent an important factor in the development of therapeutic agents for HPV-associated disease.